Associated Properties of $γ$-$π g$$γ$-closed Functions - O. Ravi; S. Margaret Parimalam; S. Murugesan; A. Pandi (International Journal of Mathematics And its Applications, 2015)
The concept of $γ$-open sets was introduced in [3,7,11]. The primary purpose of this paper is to introduce and study pre-$π gγ$-closed functions by using $γ$-open sets.